Experiences of informal women caregivers in caring for people living with HIV and AIDS in Dar es Salaam, Tanzania - Pallangyo, Eunice (Division of Nursing and Midwifery, 2017)
Aim of the study: The aim of this study was to explore and describe the experiences of informal women caregivers of people living with HIV and AIDS at home in Dar es Salaam, Tanzania. The study took place in Temeke district in the Dar es Salaam region through the auspices of Pastoral Activities and Services for people with AIDS, Dar es Salaam Archdiocese (PASADA), a non-governmental organization that provides home-based care services. Research design and method: The research design was a qualitative, descriptive and exploratory study based on the interpretive paradigm. The study population was informal women caregivers looking after spouses or relatives at home who were living with HIV and AIDS (staged at World Health Organization clinical stages III and IV), some on antiretroviral therapy and others not. Purposive sampling was used to select participants who were attending PASADA's community centre. Data were collected using semi-structured· interviews which were audio-recorded. Eight participants were interviewed in order to explore their individual experiences of caring for people living with HIV and AIDS. Data collection continued until data saturation was achieved. The recorded data were transcribed verbatim and analysed using thematic analysis. Anonymity and confidentiality of the study participants was maintained throughout. Findings: Themes which emerged from the data were as follows: social and economic situation; HIV-related stigma and discrimination; stress and burn-out: treatment and support system; care burden and the challenges. Financial problems made an impact on food security, and the caregivers also had to cope with multiple illnesses in the people under their care. The lack of support for the caregivers increases their vulnerability to stress and burn-out.